Detection of methicillin‐resistant Staphylococcus aureus (MRSA) in the microbial flora from the conjunctiva of healthy donkeys from Sicily (Italy). (23rd April 2012) - Foti, Maria; Fisichella, Vittorio; Giacopello, Cristina
Abstract Objective To describe the bacterial flora present in the normal conjunctiva of donkeys from Sicily (Italy). Animals studied A total of 46 healthy donkeys housed in 3 locations within the territory of Palermo (Sicily, Italy) were studied. Donkeys ranged from 2 to 13 years of age, with a median age of 6 years. Procedures Forty‐six conjunctival swabs were obtained from both eyes of each animal, and specimens were cultured for aerobic bacteria. Furthermore, the antimicrobial activity of methicillin (1 μg) and oxacillin (5 μg) on Staphylococcus spp. isolates was evaluated, and a specific PCR assay, which allows the detection of mecA gene specific for methicillin‐resistant Staphylococcus aureus (MRSA) strains, was performed. Results Forty of 46 (86.9%) donkeys were positive for bacteria. Eighty bacterial isolates, representing 9 bacteria genera, were successfully cultured. The most frequently recovered bacterial genus was Staphylococcus (52/80 isolates; 65%). Several strains (20/80 isolates; 25%) belonging to the Enterobacteriaceae family were also isolated, among which the most frequently isolated genus was Enterobacter (eight isolates). Of the 52 Staphylococcus spp. isolates, 14 (26.9%) strains were oxacillin/methicillin resistant. The mecA gene was detected in 6/52 (11.5%) strains. Conclusions This study contributes to the knowledge about normal ocular flora and MRSA occurrence in donkey farms in Sicily.